Ethics in Islam - Atif Khalil (St Andrews Encyclopaedia of Theology, 2025)
It may be argued that religion, in its most elemental form, comprises two dimensions: (1) a worldview or weltanschauung, that is to say, a conception about the nature and structure of reality (i.e. ‘what exists?’), and (2) a conception about the nature of the good, that is to say, a code of ethics that reflects beliefs about human meaning, purpose, and teleology (i.e. ‘what ought to be?’). In Islam, the second of these was addressed, in overlapping ways and to differing degrees, by the exponents of dialectical theology (kalām), philosophy (falsafa), Sufism (taṣawwuf), and law (fiqh). Given the breadth, scope, and internal diversity of the intellectual tradition of the faith, summarizing the essential features of an ‘Islamic ethics’ is a daunting task. The principal building blocks behind the various historical formulations of such an ethics, however, may be retraced to the Qur’an, specifically to the metaethical template of Divine Names it offers as a blueprint or guide to the qualities that must be internalized in the soul as part of the ‘good life’, mediated through the example of the Prophet Muḥammad, and to certain moral sensibilities which it summons the believer to cultivate, centred around such virtues as compassion, justice, God-consciousness, and gratitude. Through their rich, complex, and sometimes contrasting interpretations of the fundamental ethical message of the Qur’an and hadiths, generations of Muslim thinkers committed to competing theological schools (some of which were heavily indebted to the Greek legacy but all of which were united by their assent to the principle of tawḥīd) sought to respond to the fundamental question, ‘what ought to be’, and beyond that, ‘why must it be’? In the process of formulating their answers, they factored in, to various degrees, the historical conditions in which the Qur’an was revealed, its revaluation of pre-Islamic values, the relation of human to divine ethics, the precise role of the Prophet and his sunnah in the ethical transformation of the self, intentionality and the interior dimensions of human behaviour, the extent to which we are truly free and therefore morally culpable, the ontological foundations of the good, and perhaps most importantly, the epistemological question of how, as human beings, we can distinguish right from wrong, virtue from vice. All these themes shall be examined below in our attempt to outline the contours of the nature and character of ethics in Islam.